Beckett and the institution of literature - Beach, C (2004)
Beckett and the Institution of Literature investigates the evolution of Samuel Beckett's reputation over the latter half of the twentieth century, focussing on two questions: what are the institutional frameworks and operations that have effected Beckett's work, and what effect has the work had on the institution of literature? The first half of the thesis explores Beckett's relationships with his French publisher, Editions de Minuit, in the 1950s, and his English publisher, John Calder, in the 1960s. By situating Beckett in institutional and historical contexts, the thesis seeks to avoid the uncritical acceptance of Beckett's consecration that underlies so much scholarly writing on his work. Archival evidence reveals the process by which Beckett was circulated and promoted, first, to an elite avant-garde readership, and thence to a wider public, and challenges the popular conception of Beckett as utterly uninterested in publication and publicity matters. The latter half of the thesis considers the legal and promotional (particularly visual) frames of reference by which Beckett is often characterised today. It is suggested that conflicts over staging rights, and the widespread use of a uniform image of Beckett to promote his work, are instrumental both in determining and in jeopardising the work's current cultural status. The thesis argues that the relation between Beckett's work and the literary institutions that have produced it is mutually transformative, and that the work has consistently challenged, exceeded, and disrupted the institution of literature. It is proposed that there are, however, indications that the public is tiring of Beckett's now familiar classic works, and so the thesis asks why it has come about that in being canonised the work has also been domesticated, what this means for the way we have been reading Beckett's texts, and whether there is anything to be done about it.